Pengembangan Media Pembelajaran Kereta Pantun Berbasis Kearifan Lokal pada Pembelajaran Bahasa Indonesia Kelas 4 SD - Intan Wahyu Anggraini; Nanang Khoirul Umam (Departement of Mathematics Education, 2023)
This research aims to develop learning media for Pantun Train based on Local Wisdom so that Grade 4 Elementary School students are able to understand rhyme material, can distinguish types of rhymes and their examples and as a form of effort to understand the wisdom of local communities and to find out the validity of learning media for students fourth grade Elementary School. This research was conducted at SDN 30 Gresik, Kebomas District, Gresik Regency. The model used is the 4-D model developed by Thiagarajan with modifications by researchers so that it becomes three stages including define, design, and develop. The results of the research given by the validator to the Train Pantun Learning Media based on Local Wisdom in Indonesian language subjects grade 4 at SDN 30 Gresik, namely the validation of media experts I and media experts II got an average score of 96% while in the validation of material experts I and material experts II obtained an average value of 97%. The results of this study are included in the very valid category for use in the learning process of 4th grade elementary school students.